Abdominal Flap Necrosis and Wound Dehiscence following a Medical Tourist Tummy Tuck - Vladislav Pavlovich Zhitny; Noama Iftekhar; Peter Caravella; Jake Patrick Young; Barry Zide; Frank Stile (Case Reports in Surgery)
Abdominoplasty is a major surgical procedure met with high rates of patient satisfaction and improved self-image. While many patients are lured abroad due to discounted prices for such highly requested procedures, unfortunately, there are also associated complications. A 47-year-old woman presented due to abdominal scar dehiscence due to skin necrosis secondary to a discounted abdominoplasty in Mexico. The patient had been turned away by several local surgical centers for treatment of the necrosis. The patient underwent incision, drainage, and two debridements before her abdominal wound was eventually closed. Patient recovered well postoperatively with improved aesthetic result. With the rise of social media advertisements, more patients elect to receive plastic surgery abroad. Unfortunately, many of these practices are not accurately vetted and this can complicate the postoperative care especially upon return to the United States.